2011
DOI: 10.1371/journal.pone.0027780
|View full text |Cite
|
Sign up to set email alerts
|

Human Anti-V3 HIV-1 Monoclonal Antibodies Encoded by the VH5-51/VL Lambda Genes Define a Conserved Antigenic Structure

Abstract: Preferential usage of immunoglobulin (Ig) genes that encode antibodies (Abs) against various pathogens is rarely observed and the nature of their dominance is unclear in the context of stochastic recombination of Ig genes. The hypothesis that restricted usage of Ig genes predetermines the antibody specificity was tested in this study of 18 human anti-V3 monoclonal Abs (mAbs) generated from unrelated individuals infected with various subtypes of HIV-1, all of which preferentially used pairing of the VH5-51 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
57
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 39 publications
4
57
0
Order By: Relevance
“…The genes involved to the 2 MAb clones 0.5g and 5G2 are the same (the VH3-30 gene for VH and the VK2-28 gene for VL), although the lineages of the 2 clones differ. In contrast, the MAb 16G6 uses the VH5-51 gene and the llight chain, which were previously reported as the preferential genes used by anti-V3 antibodies with crosssubtype reactivity (38). The 16G6 MAb reacted not only with HIV-1 harboring the V3-tip sequence 315R, but also with HIV-1 harboring the V3-tip sequence 315Q, which is indicative of a non-subtype virus (11).…”
Section: Discussionmentioning
confidence: 93%
“…The genes involved to the 2 MAb clones 0.5g and 5G2 are the same (the VH3-30 gene for VH and the VK2-28 gene for VL), although the lineages of the 2 clones differ. In contrast, the MAb 16G6 uses the VH5-51 gene and the llight chain, which were previously reported as the preferential genes used by anti-V3 antibodies with crosssubtype reactivity (38). The 16G6 MAb reacted not only with HIV-1 harboring the V3-tip sequence 315R, but also with HIV-1 harboring the V3-tip sequence 315Q, which is indicative of a non-subtype virus (11).…”
Section: Discussionmentioning
confidence: 93%
“…Several recently described highly potent human MAbs, including PGT128, are also against the C-terminal region of V3, as well as its associ-ated glycans (26). Many of the anti-V3 MAbs are characterized by structural methods, including protein crystallography and the nuclear magnetic resonance (NMR) method (19,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). These structural studies of MAbs against the V3 crown showed that they have, in general, two antigen-binding modes.…”
mentioning
confidence: 99%
“…Together with the current 2424-V3 structure, many crystal structures of human V3 MAbs in complex with their cognate V3 epitopes have been resolved (35,(68)(69)(70) Abs can be generated in these individuals by vaccination. 2424-like Abs were not the dominant response elicited in mice upon immunization with gp120 JRFL alone or in complex with MAb, as indicated by the inability of serum Ab pools from the immunized animals to neutralize 2424-sensitive viruses such as JRFL or REJO (27), although the composition of dominant and nondominant Ab responses were not yet delineated and the gp120/MAb complex vaccines tested were not selected and optimized for presenting the 2424 epitope.…”
Section: Discussionmentioning
confidence: 99%